Impact of self-decision to stop cancer treatment on advanced genitourinary cancer patients. Issue 14 (9th April 2021) - Kobayashi, Hisato; Tsuchiyama, Katsuki; Taga, Minekatsu; Tokunaga, Takahiro; Ito, Hideaki; Yokoyama, Osamu
Abstract : Abstract: Decision-making to stop cancer treatment in patients with advanced cancer is stressful, and it significantly influences subsequent end-of-life palliative treatment. However, little is known about the extent to which the patient's self-decisions influenced the prognostic period. This study focused on the patient's self-decision and investigated the impact of the self-decision to stop cancer treatment on their post-cancer treatment survival period and place of death. We retrospectively analyzed 167 cases of advanced genitourinary cancer patients (kidney cancer: 42; bladder cancer: 68; prostate cancer: 57) treated at the University of Fukui Hospital (UFH), who later died because of cancer. Of these, 100 patients decided to stop cancer treatment by themselves (self-decision group), while the families of the remaining 67 patients (family's decision group) decided to stop treatment on their behalf because the patient's decision-making ability was already impaired. Differences in the post-cancer-treatment survival period and place of death between the 2 groups were examined. The association between place of death and survival period was also analyzed. The median survival period after terminating cancer treatment was approximately 6 times longer in the self-decision group (145.5 days in self-decision group vs 23.0 days in family's decision group, P < .001). Proportions for places of death were as follows: among the self-decision group, 42.0% of patients died at UFH, 45.0% at other medical institutions, and 13.0% at home; among the family's decision group, 62.7% died at UFH, 32.8% at other medical institutions, and 4.5% at home. The proportion of patients who died at UFH was significantly higher among the family's decision group ( P = .011). The median survival period was significantly shorter for patients who died at UFH (UFH: 30.0 days; other institutions/home: 161.0 days; P < .001). Significantly longer post-cancer-treatment survival period and higher home death rate were observed among patients whose cancer treatment was terminated based on their self-decision. Our results provide clinical evidence, especially in terms of prognostic period and place of death that support the importance of discussing bad news, such as stopping cancer treatment with patients.